ChemInform Abstract: Structural Reorganization of (Allyl‐, Benzyl‐, and Propargylsulfanyl)‐Substituted 2‐Aza‐1, 3, 5‐trienes in t‐BuOK/THF/DMSO: Access to Rare Functionalized 2‐Thiazolines. Issue 40 (30th September 2014) - Nedolya, Nina A.; Tarasova, Ol'ga A.; Albanov, Alexander I.; Trofimov, Boris A.
Abstract Different rare functionalized thiazolines along with azepine derivatives are obtained by treatment of substrates (I), (IV), and (VII) with KOtBu.